Cote d'Ivoire : Second Reviews under an Arrangement under the Extended Credit Facility and the Extended Arrangement under the Extended Fund Facility-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Cote d'Ivoire's Second Reviews Under An Arrangement Under the Extended Credit Facility (ECF) and the Extended Arrangement Under the Extended Fund Facility (EFF). Performance under the EFC/EFF-supported program was strong in the first half of 2017. All performance criteria and indicative targets for end-June 2017 were observed and all structural benchmarks were met. Sound policies implemented by the authorities in the context of the IMF-supported program have helped secure confidence of the international financial markets, which enabled a successful Eurobond issuance in June. The IMF staff supports the authorities' requests for completion of the second reviews of the program supported by the ECF and EFF arrangements.